Paediatric imaging radiation dose awareness and use of referral guidelines amongst radiology practitioners and radiographers - Portelli, Jonathan L. (Insights Imaging, 2015)
OBJECTIVES: The objectives are to investigate radiology practitioners’ and radiographers’ radiation dose awareness and use of referral guidelines for paediatric imaging examinations. METHODS: A prospective cross-sectional survey was conducted amongst radiology practitioners and radiographers working at a primary paediatric referral centre in Malta. Part of the survey asked participants to indicate the typical effective dose (ED) for several commonly performed paediatric imaging examinations, answer five true-false statements about radiation protection principles, and specify their use of referral guidelines for paediatric imaging. RESULTS: The return of 112 questionnaires provided a response rate of 66.7 %. Overall, imaging practitioners demonstrated poor awareness of radiation doses associated with several paediatric imaging examinations, with only 20 % providing the correct ED estimate for radiation-based examinations. Nearly all participants had undertaken radiation protection training, but the type and duration of training undertaken varied. When asked about the use of referral guidelines for paediatric imaging, 77.3 % claimed that they ‘did not’ or ‘were not sure’ if they made use of them. CONCLUSIONS: Poor awareness of radiation doses associated with paediatric imaging examinations and the non-use of referral guidelines may impede imaging practitioners’ role in the justification and optimisation of paediatric imaging examinations. Education and training activities to address such shortcomings are recommended. KEY POINTS: • Imaging practitioners demonstrated poor radiation dose awareness for 5 paediatric imaging examinations. • Most radiology practitioners and radiographers were ‘not sure’ or ‘did not’ use referral guidelines. • Imaging practitioners generally considered previously undertaken paediatric imaging examinations. • Some imaging practitioners had not undertaken training in radiation protection for 10 years. • Training activities to address imaging practitioners’ poor radiation dose awareness are encouraged.